Complete Freund’s adjuvant as a confounding factor in multiple sclerosis research - Lazarević, Milica; Stanisavljević, Suzana; Nikolovski, Neda; Dimitrijević, Mirjana; Miljković, Đorđe (Frontiers in Immunology, 2024)
Complete Freund's adjuvant (CFA) is used as a standard adjuvant for the induction of experimental autoimmune encephalomyelitis (EAE), the most commonly used animal model in multiple sclerosis studies. Still, CFA induces glial activation and neuroinflammation on its own and provokes pain. Additionally, as CFA contains Mycobacteria, an immune response against bacterial antigens is induced in parallel to the response against central nervous system antigens. Thus, CFA can be considered a confounding factor in multiple sclerosis-related studies performed on EAE. Here, we discuss the effects of CFA in EAE in detail and present EAE variants induced in experimental animals without the use of CFA. We put forward CFA-free EAE variants as valuable tools for studying multiple sclerosis pathogenesis and therapeutic approaches.